Innovative programs for recreational swimming and their impact on the physical development of women 30–40 years old - Шейко, Лілія (Slobozhanskyi Herald of Science and Sport, 2019)
Liliia Sheiko Purpose: to analyze the impact indicators of recreational swimming classes on the physical development of women 30–40 years old. Material & Methods: data collection was carried out in the fitness groups of the Pioneer pool sport school on water sports named after Yana Klochkova. The study involved 20 women aged 30–40 years, 2–3 times a week, attend fitness groups swimming. The duration of one lesson is 45–60 minutes. A comparative analysis of changes in the physical development of the studied contingent in the process of applying innovative programs from recreational swimming was carried out. The methods used were: survey, testing, biomedical control. The obtained quantitative data were processed by methods of mathematical statistics. Results: study suggests that in women 30–40 years old, recreational swimming classes cause positive changes in physical development. In both groups of the studied, significant changes in anthropometric indicators and indicators of the state of the cardiovascular and respiratory systems took place. Conclusions: the targeted use of innovative recreational swimming programs positively influenced the anthropometric indicators of women aged 30–40. A significant improvement in the indicators of the functional state of the cardiovascular and respiratory systems of women involved in swimming was established. It was revealed that anthropometric indicators and indicators of the functional state of the cardiovascular system after a year of classes are significantly high compared to the initial data (P(t)<0,01; P(t)<0,001).